Factors that influence employees work ethic among Malaysian civil servant in Miri, Sarawak / Nelson Kelanang Hilda - Kelanang Hilda, Nelson (Faculty of Business and Management, 2014)
Ethics in public administration has been a subject of growing interest for both researchers and practitioners interested in the future of governance. This study examined the factors that influence employee work ethic among Malaysian Civil servant in Miri,Sarawak. The purpose of this study is to determine whether Quality of Work life (QWL), Awareness of the Code of ethic, Organizational Citizenship Behavior (OCB), and Ethical leadership (EL) which is Independent Variable of the study affect employees to demonstrate ethical behavior in performing their Job. A Pilot test was conducted at Majlis Bandaraya Miri which involving 10 respondents from Administration department to test whether the instrument used are reliable. Since this study was exploratory study, the sampling design used is Convenience sampling. A total of 156 respondent has participate in the survey from different organization which is from Ibu Pejabat Polis Daerah Miri (IPDM), Kastam Diraja Malaysia Daerah Miri, Rubber Industry Smallholders Development Authority (RISDA) and from Majlis Bandaraya Miri. The finding shows that the four independents variable for the study shows that there are significant relationship with Civil servant work ethic. Summary of the finding and recommendation of the study are discussed.